Device for interim check of coordinate measuring machines - Arenhart, Rodrigo Schons; Pizzolato, Morgana; Beuren, Fernanda Hänsch; Souza, Adriano Mendonça; Cantorski da Rosa, Leandro (Metrology and Measurement systems, 2022)
This paper presents a new interim check device for coordinate measuring machines (CMMs) built from an AISI 1020 carbon steel bar with the incorporation of calibrated spheres. This artifact’s construction was made to make the interim checks of machines of this type faster and cheaper. Three devices were designed based on the ISO 10360-2 standard, the good practice guide No. 42 (NPL), and prominent authors’ research on the subject. The three options are presented in detail, but only one was built due to budget, size, and adaptability restrictions. An exploratory study was conducted to verify the device’s usability in two CMMs and concluded that the differences between the measurements are not significant. However, one machine had absolute variation values and a total standard deviation higher than the other, generating a larger expanded uncertainty.